Effect of training in peripheral blood lymphocytes and cytokine levels in elite kayakers - Borges, G. F.; Rama, L.; Pedreiro, S.; Alves, F.; Santos, A. C.; Paiva, A.; Teixeira, A. M. (International Journal of Exercise Science Conference Proceedings, 2013)
Prolonged strenuous exercise has been associated with impaired immune function. The objective of this study was to investigate the differences in the peripheral blood cell counts and cytokynes in kayakers at different moments of training. The sample consisted of eight elite male kayakers, 22± 4 years old, 77.2 kg±6.7 body mass and 177.5±5.6 cm stature. The initial VO2max was 61.2±5.5 mL.kg.min-1. The control group consisted of six healthy males, 18±1 years old, 81.3± 13.8 kg body mass and 171.9±4.5cm stature. Blood samples were collected, at rest, from the kayakers at 4 time points of the training season: t0 early November (beginning of the training season), t1 late February (after an increased volume in training load), t2 early April (after an increase in training intensity) and t4 in June (after a major competition). Blood samples from the controls were taken at 3 equivalent time-points. Lymphocyte subpopulations were determined by flow cytometry. Cytokine concentrations were determined by ELISA. Statistical analysis was done using Friedman's ANOVA- Repeated measures and the Mann-Whitney test for comparing the kaykers and control groups.